A Paddler's Guide to the Delaware River : Kayaking, Canoeing, Rafting, Tubing - Letcher, Gary (Book collections on Project MUSE., 2012)
A Paddler's Guide to the Delaware River is an indispensable resource for anyone who wants to experience the Delaware River in a kayak, canoe, raft, or tube -- or, for that matter, an automobile or an armchair. Reading the book is like travelling down the river with an experienced guide. Whether you are a novice out for an afternoon float, a seasoned adventurer on an overnight expedition, or a resident fascinated by the lore of the Delaware Valley, this book is an invaluable guide.